2020
DOI: 10.3390/insects11020108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on Age-Stage, Two-Sex Life Tables for a Minnesota-Acclimated Population of the Brown Marmorated Stink Bug (Halyomorpha halys)

Abstract: Temperature is a critical single factor influencing insect population dynamics, and is foundational for improving our understanding of the phenology of invasive species adapting to new agroecosystems or in the process of range expansion. An age-stage, two-sex life table was therefore developed to analyze fundamental demographic features such as development, survival, and reproduction of a Minnesota-acclimated population of the invasive brown marmorated stink bug (Halyomorpha halys), in the north central USA. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 67 publications
6
28
1
Order By: Relevance
“…Empirical evidence exists that these anomalies will increase with climate change, albeit more for heat waves (Timmermann et al, 1999;Easterling et al, 2000) than cold waves (but see Wang et al, 2010;Adriaan & Fitchett, 2021). Several empirical studies have, nevertheless, shown that low temperatures can affect species population phenology and fitness (Angilleta, 2009;Denlinger & Lee, 2010;Ma et al, 2017;Govindan et al, 2020), and are a major constraint to organismal function and ecological services through limiting insect activity (Denlinger & Lee, 2010). Given the historical, current, and projected climate change trajectories associated with extreme events (see Kodra et al, 2011;Jury, 2013;LTAS, 2013;Peings et al, 2013;Harnik et al, 2016;Kim & Lee, 2019), although biased toward increases in mean temperatures, low-temperature events remain a critical concern because they are likely to increase in frequency or duration concurrent with increasing mean temperature (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence exists that these anomalies will increase with climate change, albeit more for heat waves (Timmermann et al, 1999;Easterling et al, 2000) than cold waves (but see Wang et al, 2010;Adriaan & Fitchett, 2021). Several empirical studies have, nevertheless, shown that low temperatures can affect species population phenology and fitness (Angilleta, 2009;Denlinger & Lee, 2010;Ma et al, 2017;Govindan et al, 2020), and are a major constraint to organismal function and ecological services through limiting insect activity (Denlinger & Lee, 2010). Given the historical, current, and projected climate change trajectories associated with extreme events (see Kodra et al, 2011;Jury, 2013;LTAS, 2013;Peings et al, 2013;Harnik et al, 2016;Kim & Lee, 2019), although biased toward increases in mean temperatures, low-temperature events remain a critical concern because they are likely to increase in frequency or duration concurrent with increasing mean temperature (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Their rates of development, survival, longevity and reproduction depend on biotic (e.g., host plants) and abiotic factors (e.g., temperature, humidity and photoperiod). Temperature is a notable abiotic factor that facilitates the development and fecundity of the insects [ 11 , 12 , 13 , 14 ]. Many studies have introduced temperature-dependent development models based on the developmental rates of insects at different temperatures [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…While snow depth over the northernmost part of the state remains virtually unchanged, the simulations show significant decreases in snow depth along the Minnesota North Shore and into much of Wisconsin exceeding 12 cm. These regions include part of the U.S. National Forest system and are at risk of decreasing revenues in winter recreation as well as threats to ecosystem health from pests that may survive warmer winters (Govindan & Hutchison, 2020; Venette & Hutchison, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The present study describes a high‐resolution regional climate modeling effort over the U.S. state of Minnesota that is already providing input for various projects, including improved projections of weather extremes, management of infrastructure, industry, and water resources (Noe et al., 2019) as well as the tracking of invasive species (Govindan & Hutchison, 2020; Venette & Hutchison, 2021). This state‐level downscaling effort links climate projections to decision‐making within regional communities.…”
Section: Discussionmentioning
confidence: 99%